2009
DOI: 10.1158/0008-5472.can-09-0026
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Expression in Prostate Cancer Cells Is Suppressed by Activation of Epidermal Growth Factor Receptor and ErbB2

Abstract: Prostate cancers (PCa) that relapse after androgen deprivation therapies [castration-resistant PCa (CRPC)] express high levels of androgen receptor (AR) and androgen-regulated genes, and evidence from several groups indicates that ErbB family receptor tyrosine kinases [epidermal growth factor (EGF) receptor (EGFR) and ErbB2] may contribute to enhancing this AR activity. We found that activation of these kinases with EGF and heregulin-β1 rapidly (within 8 hours) decreased expression of endogenous AR and androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
(53 reference statements)
5
41
0
Order By: Relevance
“…20 It has also been reported that the EGFR family modulates AR signaling and contributes androgenindependent tumor progression. [24][25][26][27][28] Expression levels of EGFR family were therefore evaluated as possible targets for NEU3 ( Figure 4d). NEU3 was found to increase EGFR and ERBB2 in mRNA and protein levels together with AR and PSA elevation in LNCaP cells under androgendeficient conditions, although they behaved differently in the presence of DHT.…”
Section: Resultsmentioning
confidence: 99%
“…20 It has also been reported that the EGFR family modulates AR signaling and contributes androgenindependent tumor progression. [24][25][26][27][28] Expression levels of EGFR family were therefore evaluated as possible targets for NEU3 ( Figure 4d). NEU3 was found to increase EGFR and ERBB2 in mRNA and protein levels together with AR and PSA elevation in LNCaP cells under androgendeficient conditions, although they behaved differently in the presence of DHT.…”
Section: Resultsmentioning
confidence: 99%
“…These include IL 6 R, EGFR, TGFbR1 and TGFbR2, IGFR, FGFR, and VEGFR. Cross-talk between tyrosine kinase receptors (TKR) and AR takes place via specific and overlapping pathways (Cai et al, 2009). Furthermore, sensitisation of the androgenic response by multi-functional growth factor signalling pathways is thought to be one of the mechanisms through which AR contributes to the emergence of androgen-independent prostate tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of AR gene expression can be mediated by ErbB kinases (26) or the Purα transcriptional repressor (27). Among the remaining known factors, androgen itself plays a complex role in regulating AR levels.…”
Section: Figurementioning
confidence: 99%